Tracked Changes. Safety of machinery. Electro-sensitive protective equipment. Particular requirements for equipment using vision based protective devices (VBPD). Additional requirements when using reference pattern techniques (VBPDPP) Part 4-2, (3rd May 2023) - British Standards Institution,
No abstract available